The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1678-7757-2018-0316
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease, peri-implant disease and levels of salivary biomarkers IL-1β, IL-10, RANK, OPG, MMP-2, TGF-β and TNF-α: follow-up over 5 years

Abstract: Objective The aim of this study was to evaluate the levels of salivary biomarkers IL-1β, IL-10, RANK, OPG, MMP-2, TG-β and TNF-α in individuals with diagnosis of peri-implant mucositis in the absence or presence of periodontal and peri-implant maintenance therapy (TMPP) over 5 years. Material and Methods Eighty individuals diagnosed with peri-implant mucositis were divided into two groups: one group that underwent periodontal and peri-implant regularly maintenance thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…A recent study showed that elevated salivary levels of C-reactive protein and TNF-α have been significantly associated with type 2 diabetes [ 25 ]. Several studies have indicated elevated levels of TNF-α in patients with periodontitis, peri-implant disease, oral squamous cell carcinoma, and oral candidiasis [ 26 , 27 , 28 ]. In our study we obtained significantly increased salivary TNF-α values in diabetics compared to controls at baseline and at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that elevated salivary levels of C-reactive protein and TNF-α have been significantly associated with type 2 diabetes [ 25 ]. Several studies have indicated elevated levels of TNF-α in patients with periodontitis, peri-implant disease, oral squamous cell carcinoma, and oral candidiasis [ 26 , 27 , 28 ]. In our study we obtained significantly increased salivary TNF-α values in diabetics compared to controls at baseline and at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, markers indicating peri-implant tissue destruction (RANK, RANKL, Mmp1α, Mmp2 and Mmp9) were significantly increased in Ti64 corroded samples compared to control Ti (Figure 8). It is known that the persistent secretion of pro-inflammatory cytokines such as IL-1b and TNFα is associated with bone resorption surrounding dental implants (Trombone et al, 2016;Gomes et al, 2019), as well as the increased transcription of MMP genes (Trombone et al, 2016). Additionally, patients with orthopedic implant aseptic loosening present elevated levels of IL-1b, IL-8, and TNFα in their synovial fluid, which is also associated with tissue destruction (Hernigou et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…One research showed increased salivary TNF-α level in cases with peri-implant clinical condition, especially in patients with peri-implantitis [ 35 ]. Another research confirmed significantly higher serum level of TNF-α in peri-implantitis patients compared to controls, indicating the pivotal role of these cytokines in peri-implantitis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%